Iraqi E-Voting System Based on Smart Contract Using Private Blockchain Technology - Jumaa, Maral Hassan; Shakir, Ahmed Chalak (Informatica, 2022)
In democratic societies including Iraq, electronic voting (e-voting) is an available option as a viable voting system. This system is more economically advisable than face-to-face voting by eliminating the need to pay poll staff. It may also make voting more accessible to the population with impairments and those living overseas. This study will propose an e-voting system based on smart contracts by using a decentralized private Blockchain. The proposed e-voting system will provide transparency, accuracy, fairness, eligibility, anonymity, verifiability, and immutability. This research proposed the most secure way of voting with the help of Blockchain using a mobile application that can be used to implement a large-scale solution and cost-effective. The Blockchain-based system has been designed in conjunction with the existing ECC cryptosystem to assure the dependability, anonymity, and security of votes and voters. The system that has been developed can be used to properly conduct elections, using a quick response code (QR Code), face recognition, and fingerprint for identification before casting a ballot to ensure eligibility. This results in using mobile smartphones in the voting process where voters can observe the transparency of their votes. Furthermore, eliminates the possibility of fraud and manipulation of the votes made due to the used blockchain for secure storage.